RNAi-based functional elucidation of PtrPRP, a gene encoding a hybrid proline rich protein, in cold tolerance of Poncirus trifoliata - Peng, Ting; Jia, Mao-Mao; Liu, Ji-Hong (Frontiers in Plant Science, 2015)
Hybrid proline-rich proteins (HyPRPs) have been suggested to play important roles in various plant development and stress response. In this study, we report the cloning and functional analysis of PtrPRP, a HyPRP-encoding gene of Poncirus trifoliata. PtrPRP contains 176 amino acids, among which 21% are proline residues, and has an 8-cysteine motif (8 CM) domain at the C terminal, a signal peptide and a proline-rich region at the N terminal. PtrPRP is constitutively expressed in root, stem and leaf, with the highest expression levels in leaf. It was progressively induced by cold, but transiently upregulated by salt and ABA. Transgenic P. trifoliata plants with knock-down PtrPRP by RNA interference (RNAi) were generated to investigate the role of PtrPRP in cold tolerance. When challenged by low temperature, the PtrPRP-RNAi plants displayed more sensitive performance compared with wild type (WT), as shown by higher electrolyte leakage and malondialdehyde content. In addition, the RNAi lines accumulated more reactive oxygen species (ROS) and lower levels of proline relative to WT. These results suggested that PtrPRP might be positively involved in cold tolerance by maintaining membrane integrity and ROS homeostasis.